IDENTIFIKASI PERKEMBANGAN INFRASTRUKTUR DI KECAMATAN JATI AGUNG (STUDI KASUS: DESA JATIMULYO, DESA WAY HUWI DAN DESA BANJAR AGUNG) - Adinda Sekar Tanjung; Almasa, Fazilet (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
Regional development is caused by various factors such as university areas and Toll Gate. Jati Agung District experienced quite rapid development after the operation of the ITERA Campus and the ITERA Kotabaru Toll Gate. Developments were identified from the increase in the number of built-up land in villages around ITERA, namely Way Huwi Village, Banjar Agung Village and Jatimulyo Village. The increase in built-up land in the form of housing is certainly correlated with an increase in population so this needs to be balanced with adequate residential infrastructure. Therefore, this research aims to identify the development of existing residential infrastructure in Jati Agung District, whether it is in line with the development of the area. The identified infrastructure includes road networks, telecommunications, waste, trade, parks and fields, worship, and health. Identification of infrastructure developments is carried out by collecting secondary data from agencies and processing Google Earth image data. The interview method with the South Lampung PUPR Service and village officials was carried out to support the results of secondary data processing. The research results show that there are several quantity of infrastructures that not develop such as garbage dumps (TPS), community health centers, shopping centers whose existing service coverage does not yet cover the study area settlements. There has been a significant development in the quantity of infrastructure such as neighborhood roads, BTS, shops, mosques and pharmacies. Lesson learned from this study is to show the availability of infrastructure that needs to be compared with the infrastructure needs of the region and become input for stakeholders for the provision and improvement of the quality of the infrastructure.